2011
DOI: 10.3109/00365548.2010.545835
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of atazanavir/ritonavir compared with lopinavir/ritonavir in treatment-naïve human immunodeficiency virus-1 patients in Sweden

Abstract: The results indicate that atazanavir/r is cost-saving and more effective compared to lopinavir/r for patients who have previously not been exposed to antiretroviral drugs in Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…However, this decision was likely to have overestimated the efficacy of the antibiotic strategies in our model, biasing our results away from FMT. The utilities for mild-moderate and severe CDI had to be extrapolated from other comparable causes of diarrhea, as there are no published estimates of health utility with CDI [41,42]. Finally, the costs attributed to FMT in our analysis included those related to donor screening and instillation of stool, but not the infrastructure and personnel costs required in establishing an FMT program.…”
Section: Discussionmentioning
confidence: 99%
“…However, this decision was likely to have overestimated the efficacy of the antibiotic strategies in our model, biasing our results away from FMT. The utilities for mild-moderate and severe CDI had to be extrapolated from other comparable causes of diarrhea, as there are no published estimates of health utility with CDI [41,42]. Finally, the costs attributed to FMT in our analysis included those related to donor screening and instillation of stool, but not the infrastructure and personnel costs required in establishing an FMT program.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a trial which compared ATV or ATV/r with other PIs had demonstrated the superiority of ATV or ATV/r based cART to suppress the virus below 50 copies/ml 26 . A multinational prospective observational study in high-income countries also reported a lower risk of hazard ratio for death, AIDS-defining illness and virological failure to ATV/r than LPV/r 27 . Moreover, an economic evaluation from Sweden found the dominance of ATV/r based regimens over LPV/r 28 .…”
Section: Discussionmentioning
confidence: 92%
“…This study was conducted from the hospital perspective. Cost estimates ( Table 2 1 , 14 , 62 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ) were derived from the literature and converted into 2018 US dollars using the Personal Consumption Expenditure Health Index. 141 Fixed and variable costs were considered.…”
Section: Methodsmentioning
confidence: 99%
“… 132 , 133 Since there is no established utility measure of CDI in the United States, this followed a standard practice of basing it on that of noninfectious diarrhea. 123 , 124 , 125 , 126 , 127 A loss in QALYs owing to time spent in a hospital admission was accounted for with a 0.63 utility value for hospitalized patients, derived using the EuroQol-5D instrument. 134 Thus, it was possible to have a net negative QALY, despite a minimally net positive CDI averted.…”
Section: Methodsmentioning
confidence: 99%